2021
DOI: 10.1002/jum.15764
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Shear Wave Speed Assessment for Muscles With the Diagnosis of Taut Bands and/or Myofascial Trigger Points Using Probe Oscillation Shear Wave Elastography: A Pilot Study

Abstract: Objective To use probe oscillation shear wave elastography (PROSE) with two vibration sources to generate two shear waves in the imaging plane to quantitatively assess the shear wave speeds (SWSs) of muscles with and without the diagnosis of taut bands (TB) and/or myofascial trigger points (MTrPs). Methods Thirty‐three patients were scanned with the PROSE technique. Shear waves were generated through continuous vibration of the ultrasound probe, while the shear wave motions were detected using the same probe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The high reliability of our shear wave elastography measurements supports the use of these methods for effectively distinguishing between changes in muscle properties due to pathological conditions versus normal variability. Our study's demonstration of moderate-to-good reliability in shear wave elastography measurements can be directly applied to clinical settings where myofascial trigger points might be evaluated [44][45][46][47][48]. Given that myofascial trigger points are notably prevalent in patients with cervical musculoskeletal conditions [49][50][51][52][53][54], the ability to reliably measure muscle stiffness and elasticity can greatly enhance the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…The high reliability of our shear wave elastography measurements supports the use of these methods for effectively distinguishing between changes in muscle properties due to pathological conditions versus normal variability. Our study's demonstration of moderate-to-good reliability in shear wave elastography measurements can be directly applied to clinical settings where myofascial trigger points might be evaluated [44][45][46][47][48]. Given that myofascial trigger points are notably prevalent in patients with cervical musculoskeletal conditions [49][50][51][52][53][54], the ability to reliably measure muscle stiffness and elasticity can greatly enhance the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Lok et al. employed probe oscillation SWS and reported that muscles with taut bands had higher shear wave velocities than those without [ 22 ]. The authors speculated that the increase in stiffness was due to persistent local muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly intriguing since the levator scapulae is frequently reported as tender among adults suffering from nonspecific neck pain ( 53 ). A potential limitation of the included studies is the lack of control for myofascial trigger points, which are also associated with increased elastography-based stiffness scores ( 54 ). Such active trigger points appear more frequently in the upper trapezius (40%) compared to the levator scapulae (15%) in those with mechanical neck pain ( 55 ).…”
Section: Discussionmentioning
confidence: 99%